2011
DOI: 10.1111/j.1365-2486.2011.02533.x
|View full text |Cite
|
Sign up to set email alerts
|

Fire‐induced tree mortality in a neotropical forest: the roles of bark traits, tree size, wood density and fire behavior

Abstract: Large-scale wildfires are expected to accelerate forest dieback in Amazô nia, but the fire vulnerability of tree species remains uncertain, in part due to the lack of studies relating fire-induced mortality to both fire behavior and plant traits. To address this gap, we established two sets of experiments in southern Amazonia. First, we tested which bark traits best predict heat transfer rates (R) through bark during experimental bole heating. Second, using data from a large-scale fire experiment, we tested th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
262
4
11

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 257 publications
(290 citation statements)
references
References 37 publications
13
262
4
11
Order By: Relevance
“…We assessed the impact of these variables on woody species' regeneration and survival, diversity, and community composition. The results reported here build on long-term research in the area, testing the hypothesis that repeated fires may push forests to a tipping point beyond which they are converted to savanna-like ecosystems (Balch et al , 2011Brando et al 2012;Massad et al 2013). This work extends the findings of Massad et al (2013) which reported on regeneration during the first 6 months of seedling establishment after repeated fire.…”
Section: Introductionsupporting
confidence: 65%
“…We assessed the impact of these variables on woody species' regeneration and survival, diversity, and community composition. The results reported here build on long-term research in the area, testing the hypothesis that repeated fires may push forests to a tipping point beyond which they are converted to savanna-like ecosystems (Balch et al , 2011Brando et al 2012;Massad et al 2013). This work extends the findings of Massad et al (2013) which reported on regeneration during the first 6 months of seedling establishment after repeated fire.…”
Section: Introductionsupporting
confidence: 65%
“…These findings confirm that fire-related impacts in Amazonian forests are more persistent than previously recorded in the literature (up to three years; [15]). However, very little is still known about the fate of forest biomass and carbon stocks following forest fire events considering the long-term dynamics of vegetation that remain in these areas [15,16]. LiDAR, therefore, is a powerful technology to further explore these impacts.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, mortality rates in forests affected by fires are significantly different from zero, two to three years after the fire event [16]. Nevertheless, capturing these long-term impacts of fires on tropical forests in a systematic way remains a challenge because of the difficulty in obtaining complex forest structure information over large areas, as well as the frequency of fire events and ecological processes [15,17].…”
Section: Introductionmentioning
confidence: 99%
“…Fire is naturally important in this region as it helps to maintain the cerrado ecosystem, but, with increasing demands for agricultural and pasture land, fire is used as a tool to remove unwanted biomass, and it often degrades forests via escaped fires (Nepstad et al 1999). This has increased fire frequencies in the southern Amazon above historical levels, particularly during drought years (Bush et al 2008). These human impacts and a lack of protected areas combine to place the seasonally-dry forest of the southern Amazon among the most vulnerable of the Amazonian ecoregions (SoaresFilho et al 2006), particularly because predictions for this area suggest temperature will increase and precipitation will decrease-a combination that will result in increased fire potential (Malhi et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Many fires escape into the forest, where they tend to burn the surface litter layer (i.e. they do not become crown fires) and cause tree mortality by exposing the base of the tree to a low-intensity fireline (Brando et al 2011). The region experiences a dry season between May and September (Nimer 1989), and more than 95 % of the 1,900 mm annual precipitation falls during the rainy season (F. Bäse, personal communication).…”
Section: Introductionmentioning
confidence: 99%